APPROXIMATION OF FOURIER SERIES OF A FUNCTION OF LIPCHITZ CLASS BY PRODUCT MEANS - Misra, M. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Lipchitz class of function had been introduced by McFadden[5}.Recently dealing with degree of approximation of Fourier series of a function of Lipchitz class Nigam[12] and Misra et al.[13] have established certain theorems. Extending their results in this paper a theorem on degree of approximation of a function by product summability has been established